Differential pattern of indigenous microbiome responses to probiotic Bifidobacterium lactis V9 consumption across subjects. (October 2020) - Ma, Chenchen; Huo, Dongxue; You, Zhengkai; Peng, Qiannan; Jiang, Shuaiming; Chang, Haibo; Zhang, Jiachao; Zhang, Heping
Graphical abstract: Highlights: Baseline differences of gut microbiota determine the response for the probiotic. Anti-Engraftment Index was used to predict the persistence ability of the probiotic. Pay attention to strain-specific and cohort-specific studies in probiotics research. Abstract: Various factors, including those associated with the host and environment, should be considered to further explore the health-promoting effects of probiotics. However, it is important to consider persistence as a basic but crucial factor in the function of probiotics in the gut. To date, few studies have investigated the factors that influence probiotic persistence. To address these challenges, we designed a cohort experiment that included 49 subjects and used the probiotic Bifidobacterium lactis V9 to identify intestinal microbiota related to probiotic persistence based on high-throughput amplicon sequencing. All of the subjects were divided into three groups (Persisters, Temporary and Non-Persisters) according to the detected amount of viable Bifidobacterium lactis V9 in their faeces. Accordingly, the intestinal microbiota fluctuations in the Persisters group were significant and persistent, whereas those observed in the Non-Persisters group were limited. At the genus level, up to seven genera changed significantly in Persisters group, whereas only the genus Anaerobacterium changed significantly in Non-Persisters group throughout the experiment. At baseline, we observed highly distinct microbial alpha diversity and taxonomic features between the Persisters and Non-Persisters groups. A total of 12 genera were associated with probiotic persistence, with Bifidobacterium and eight other genera negatively associated with probiotic persistence and Anaerobacterium, Paraprevotella and Erysipelatoclostridium positively associated with probiotic persistence. Based on these potential biomarkers, an "Anti-Engraftment Index" (AEI) was derived to classify and predict probiotic persistence in test and validation cohorts with high accuracy. However, we also observed that the AEI did not work in other probiotic consumption experiments, indicating that the AEI was strain-specific.